If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 = -22x + 8x Combine like terms: -22x + 8x = -14x 42 = -14x Solving 42 = -14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14x' to each side of the equation. 42 + 14x = -14x + 14x Combine like terms: -14x + 14x = 0 42 + 14x = 0 Add '-42' to each side of the equation. 42 + -42 + 14x = 0 + -42 Combine like terms: 42 + -42 = 0 0 + 14x = 0 + -42 14x = 0 + -42 Combine like terms: 0 + -42 = -42 14x = -42 Divide each side by '14'. x = -3 Simplifying x = -3
| 3x+159y=1000 | | 0.08+0.06(x+9)=1.24+2.3 | | 4*(2*y)+2*y=116 | | y/6.25=16/87 | | -2y=16 | | -7(z+3)+3z=0 | | (7-14)*(-12-8)/4 | | 9y-4y=10 | | -45.3+(-71.8)= | | -9y-2y-10=6+5y | | 4*(2*y)+2*y=68 | | 4*(2*y)+2*y=106 | | -7.34+39.79= | | 6(v-1)=2v+3-3(-6v-1) | | 2500-2x^2-x=0 | | -0.1x=0.14 | | 2500-2x^2=x | | x^2-8x-300=0 | | 4(-24+8c)=64 | | 5y-3(y-3)+6=0 | | 2500x-2x^2=0 | | 7.9-49.35= | | 9x+8.44=2x+16 | | 16.7+(-3.3)= | | -9y-2(y+5)=6+5y | | -4(-4w+6)-4w=6(w-3)-8 | | 12x+77y=11 | | y-1.8=1 | | -4(-4w+6)-4w=6(w-3) | | 6+3x=12/2 | | -10x+-7x= | | 800x-0.29=300x+0.46 |